SAT0530 Methotrexate for Maintenance of Remission in IgG4-Related Disease. (9th June 2015) - Della Torre, E.; Campochiaro, C.; Ramirez, G.; Berti, A.; Lanzillotta, M.; Bozzolo, E.; Dagna, L.; Sabbadini, M.G.
Abstract : Background: IgG4-related disease (IgG4-RD) is a relapsing-remitting fibro-inflammatory disorder that dramatically responds to corticosteroids but oftentimes relapses while tapering these medications. Corticosteroid refractoriness appears to be more common in patients with extrapancreatic disease. Experience with disease-modifying antirheumatic drugs as steroid-sparing agents is lacking. Objectives: We aimed to assess the efficacy of methotrexate (MTX) in maintaining steroid-induced remission of IgG4-RD with systemic involvement. Methods: The present study included 10 subjects with biopsy proven IgG4-RD followed between January 2008 and May 2014. At IgG4-RD relapse MTX (up to 20 mg/week) was added to conventional steroid therapy. Efficacy of MTX in maintaining steroid induced remission was assessed at 6 and 12 months by (i) IgG4-RD Responder Index (IgG4-RD RI), (ii) patient's ability to taper or stop prednisone, (iii) total IgG and IgG subclasses, and (iv) radiological imaging. An improvement of the IgG4-RD RI of more than 2 points and an overall IgG4-RD RI <3 after therapy defined partial (PR) and complete (CR) remission, respectively. Paired t-test was used to compare variables at disease relapse, 6 and 12 months after MTX introduction. A p value <0.05 was considered statistically significant. Results: Patients' cohort included 5 males and 5 females, with a mean age of 65 years at the time of diagnosis (range 51 – 75 years). Organ involvement included pancreas, biliary tree, aorta, salivary glands (submandibular and parotid), lacrimal glands, lymph nodes, pachymeninges and retroperitoneum. IgG4-RD relapse occurred on average 7 months (range 2-10 months) after the diagnosis, at a mean steroid daily dosage of 9.6 mg (range 0-20 mg). The mean IgG4-RD RI and serum IgG4 concentration at disease relapse were 8.5 (range 3-15) and 666 mg/dL (range 46-2500 mg/dL), respectively. Oral prednisone at a starting dose of 1mg/kg for 3 weeks induced CR in 4 patients and PR in 6. After 3 weeks of prednisone, the mean IgG4-RD RI, serum IgG4 level, and daily dosage of prednisone were 2.75 (range 1-6), 513 mg/dL (19-1500 mg/dL) and 5 mg (range 0-10 mg), respectively (p value <0.05 for all variables when compared to their values at disease relapse). MTX was introduced on average 5 weeks (range 1-16 weeks) after initiation of corticosteroid therapy and escalated to a dosage of 20 mg/week. The mean daily dosage of prednisone at the time of MTX introduction was 20.75 mg (range 10-50 mg). Six months after MTX introduction 3 patients in CR were able to stop glucocorticoid treatment. Twelve months after MTX initiation, 5 patients were in CR without prednisone; 5 were in PR on prednisone 5 mg/day. No relapses occurred under MTX. Conclusions: Treatment with methotrexate represents a promising strategy for maintaining steroid-induced remission in patients with IgG4-RD. References: Khosroshahi A, Stone JH. Treatment approaches to IgG4-related systemic disease. Curr Opin Rheumatol 2011;23(1):67-71. Acknowledgements: The authors thanks Prof John H Stone from the Massachusetts General Hospital (Boston) for the helpful inputs. Disclosure of Interest: None declared